Tetraazamacrocyclic derivatives and their metal complexes as antileishmanial leads. (1st May 2019) - Hubin, Timothy J.; Walker, Ashlie N.; Davilla, Dustin J.; Carder Freeman, TaRynn N.; Epley, Brittany M.; Hasley, Travis R.; Amoyaw, Prince N.A.; Jain, Surendra; Archibald, Stephen J.; Prior, Timothy J.; Krause, Jeanette A.; Oliver, Allen G.; et al.
Graphical abstract: Several bis-aryl-monocyclic polyamines and their metal complexes were shown to be potent in vitro inhibitors of Leishmania donovani . The synthesis of the two most promising compounds, FeL7 Cl2 and MnL7 Cl2, are shown below. Abstract: A total of 44 bis-aryl-monocyclic polyamines, monoaryl-monocyclic polyamines and their transition metal complexes were prepared, chemically characterized, and screened in vitro against the Leishmania donovani promastigotes, axenic amastigotes and intracellular amastigotes in THP1 cells. The IC50 and/or IC90 values showed that 10 compounds were similarly active at about 2-fold less potent than known drug pentamidine against promastigotes. The most potent compound had an IC50 of 2.82 µM (compared to 2.93 µM for pentamidine). Nine compounds were 1.1–13.6-fold more potent than pentamidine against axenic amastigotes, the most potent one being about 2-fold less potent than amphotericin B. Fourteen compounds were about 2–10 fold more potent than pentamidine, the most potent one is about 2-fold less potent than amphotericin B against intracellular amastigotes in THP1 cells. The 2 most promising compounds (FeL7 Cl2 and MnL7 Cl2 ), with strong activity against both promastigotes and amastigotes and no observable toxicity against the THP1 cells are the Fe 2+ - and Mn 2+ -complexes of a dibenzyl cyclen derivative. Only 2 of the 44 compounds showed observable cytotoxicity against THP1 cells. Tetraazamacrocyclic monocyclic polyamines represent a new class of antileishmanial lead structures that warrant follow up studies.